Job networks in Izmir: Why are migrants different? - Alper Duman; Idil Göksel (Izmir University of Economics, Department of Economics, 2015)
The aim of this paper is to investigate the network effect on the probability of finding employment. This paper uses a specific data set from the Izmir region, prepared by the Turkish Statistical Institute for a specific project carried out by Izmir University of Economics in cooperation with the Izmir Chamber of Commerce, the Izmir branch of theTurkish Statistical Institute and the Turkish Labour Institute. Izmir, the third biggest city in Turkey, attracts both skilled and unskilled migrants, and has become one of the preferred destinations for migrants. The relative success of migrants in employment relates to their use of job search channels. We differentiate job search channels into formal/individual, and network forms. The latter refers to the job referral or job information diffusion through relatives and acquaintances. We find that migrants benefit from a comparative advantage in the usage of the network channel. Moreover, this network advantage is more robust for less educated workers.
Keywords: J15; J61; D83; 330; Social networks; migrants; Izmir